(untitled) (Estudios Sociales, 2020)
We intend to do a comparative study of the invention of flag day in Mexico and Argentina. In both cases, there were processes that occurred between 1934 and 1940 or so. The demand that there be a day dedicated to the worship of national flags arose from the fear of some groups that "communism" would replace with their red flags those of the homelands. Behind this apparent similarity are notorious differences: these are different political contexts, in the Argentine case it is a government with ideological traits related to anti-communism and the initiative arises from sectors of conservative elites. In Mexico the government of Lázaro Cardenas was a radical democracy in the social and ideological and the initiative arises from conservative groups of Catholic popular sectors